Pengaruh Partisipasi Masyarakat Terhadap Efektivitas Program Sanitasi Berbasis Masyarakat (Sanimas) Di Kelurahan Tegal Sari Mandala Iii Kecamatan Medan Denai - Rizka Amaliah; Robinson Sembiring (SAJJANA: Public Administration Review, 2023)
The purpose of this research is to analyze the influence of community participation which includes the participation of ideas, participation of personnel, participation of property, participation of skills and skills, and social participation on the effectiveness of the SANIMAS program in Tegal Sari Mandala III Village. This study uses a quantitative approach involving 55 respondents and data analysis using a Structural Equation Modeling (SEM) system. The results of this study indicate that community participation has a positive and significant effect on the effectiveness of the SANIMAS program in Tegal Sari Mandala III Village, as evidenced by a T-statistic of 66,520 (> 1.64). Based on the calculation of the coefficient of determination, the R2 value is 0.860 which indicates that the community participation variable is able to contribute to the effectiveness variable of 86%.